2000
DOI: 10.1097/00007632-200009150-00020
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and Patients’ Preferences and Concerns in Idiopathic Adolescent Scoliosis

Abstract: Although parents and patients had similar ratings and concerns, the parents' concerns were higher, and expectations were greater than the patients'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 15 publications
4
75
1
1
Order By: Relevance
“…[13][14][15] Bridwell et al reported that cosmesis ranked second as the reason for surgery among both parents and patients. 16 Patients' perception of their body image affects their psychosocial health as scoliosis patients have been shown to have lower scores in various quality-of-life questionnaires compared to healthy adolescents. 17,18 Patients will closely observe their own physical appearance and make a comparison with adolescents without scoliosis in terms of negative body image, body shape and body size.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Bridwell et al reported that cosmesis ranked second as the reason for surgery among both parents and patients. 16 Patients' perception of their body image affects their psychosocial health as scoliosis patients have been shown to have lower scores in various quality-of-life questionnaires compared to healthy adolescents. 17,18 Patients will closely observe their own physical appearance and make a comparison with adolescents without scoliosis in terms of negative body image, body shape and body size.…”
Section: Discussionmentioning
confidence: 99%
“…The included questions were based on the validated Dallas Pain Questionnaire and on a widely used LBP scale. For the attitudinal indicators, we focused on current situation regarding pain and impact on their lives, as the literature points to more pain and everyday problems as a motivation for preferring surgery (Bederman et al, 2010;Bridwell et al, 2000;Lurie et al, 2008;Turner et al, 1998). A similar effect on preferences has been shown for patients with longer pathways and more experience with different non-surgical treatments (Lurie et al, 2008).…”
Section: Have Cut the Text Above The Screenshotmentioning
confidence: 99%
“…3 Co-operation with a national self-help association gave us the opportunity to evaluate the longterm status of patients with idiopathic scoliosis independently of different treatment protocols. The disadvantage of the design of our study was that we were not able to obtain the original Cobb angle in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients and their parents are concerned about the long-term effects of an extensive fusion in terms of spinal function, the development of degenerative arthritis and pain. 3 To address these concerns, the long-term results in patients who have scoliosis and have had a fusion must be compared with those who have not, and with a control group. 1 To date, there have been several such long-term studies on extended spinal fusion.…”
mentioning
confidence: 99%